Home gardens agrobiodiversity in the Colombian Andes - Montenegro R., Milena; Lagos B., Tulio César; Vélez L., Jorge (Revista de Ciencias Agrícolas, 2017)
Home gardens are important, since they are a source of genetic resources, ancestral knowledge and food security for mankind. The objective of this study was to characterize the agrobiodiversity of home gardens in a zone of the Colombian Andes(Ancuya, Nariño), located at 1 ° 15’59, 52’’N, 77° 31’63’’W. We sampled 120 properties in 13 veredas, where we applied semi-structured surveys with 31 variables. The information was processed through multiple correspondence (MCA) and cluster analyses. To study the floristic composition of the home garden types, we used the minimal area methodology. In addition, we measured the diameter at breast height (DBH) of the woody species, and species with DBH ≥ 10cm were considered. Ecological variables such as frequency, dominance, richness, and importance value index (IVI) were estimated. We identified five factors that explained 30.39% of the variability, where factor one was predominant and included variables that related to the species diversity present in the home gardens. We conclude that 142 species, including trees, shrubs, and food and medicinal crops, belonging to 126 genera and 66 families, were found in the floristic composition of the home garden types. The predominant family is Lamiaceae with 10 species.